INTELEKTUAL DALAM DUNIA ISLAM MODERN: TRANSMISI, TRANSFORMASI, KOMUNIKASI - Bulqis Bulqis; Yusuf Hanafi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This article is a review of the book titled "Intellectuals In The Modern Islamic World: Transmission, Transformation, Communication", edited by Stephane A. Dudoignon, Komatsu Hisao, and Kosugi Yasushi. The book presents an in-depth exploration of the history and typology of intellectuals in the Islamic world during the modern and contemporary periods, from the late 19th century to the present day. The book consists of two main parts. The first part focuses on the journal al-Manar, which was published between 1898 and 1935 and read by a diverse audience across the Islamic world. It inspired the imagination and arguments of local intellectuals in the first half of the twentieth century. The second part focuses on the formation, transmission, and transformation of learning and authority, from the Middle East to Central and South Asia, throughout the twentieth century. Thus, the book makes a significant contribution to the understanding of the dynamics of Islamic thought and the role of intellectuals in responding to the challenges of modernity